(untitled) (Medico Legal Update, 2021)
Background: Activated partial thromboplastin time and prothrombin time measures the action of the intrinsic and extrinsic pathways of coagulation needed to maintain homeostasis in the body. We studied aPTT and PT levels in acute myocardial infarction (AMI) patients on anticoagulation therapies and normal subjects. The aim of the study is to assess aPTT and PT in patients of acute MI on anticoagulation. Materials And Method: This study was conducted on 42 patients with chest pain and 84 AMI patients, admitted to Dhiraj hospital, Vadodara. The AMI patients were classified into STEMI (n=28) and NSTEMI (n=56). PT and aPTT were assayed on a fully automatic Stago-coagulometer instrument (STA Compact Max). Conclusion: Patients with STEMI had mean aPTT of 40.79 ± 1.83 s, NSTEMI had 41.33 ± 2.06 s, aPTT in control subjects was 31.35 ± 0.48 s. Patients with acute coronary syndrome had significantly higher levels of aPTT. Patients with STEMI has PT of 17.42 ± 5 s, NSTEMI had 18.56 ± 5 s. Patients on anticoagulation therapy had higher aPTT and PT values.Both PT and aPTT are high in acute MI patients on anticoagulants. The elevations in PT values were more than 3 fold greater than aPTT suggesting that PT has a higher sensitivity for predicting blood clotting capacity in patients already on anticoagulations.